2018
DOI: 10.3758/s13421-018-0852-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of look-backs in the processing of written sarcasm

Abstract: Previous eye-tracking studies suggest that when resolving the meaning of sarcastic utterances in a text, readers often initiate fixations that return to the sarcastic utterance from subsequent parts of the text. We used a modified trailing mask paradigm to examine both the role of these look-back fixations in sarcasm comprehension and whether there are individual differences in how readers resolve sarcasm. Sixty-two adult participants read short paragraphs containing either a literal or a sarcastic utterance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 75 publications
3
29
1
Order By: Relevance
“…This procedure was then repeated until the whole paragraph had been presented (see Figure 4a for an illustration of the method). To avoid delays due to having to fixate exactly within the square, the line check was triggered immediately after participants' gaze moved to 6 It should be noted that Olkoniemi, Johander, and Kaakinen (2018) have recently also used the trailing mask paradigm in a paragraph-reading study. However, in their experiment the trailing mask was triggered at the sentence level and not word-by-word as in the present research.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was then repeated until the whole paragraph had been presented (see Figure 4a for an illustration of the method). To avoid delays due to having to fixate exactly within the square, the line check was triggered immediately after participants' gaze moved to 6 It should be noted that Olkoniemi, Johander, and Kaakinen (2018) have recently also used the trailing mask paradigm in a paragraph-reading study. However, in their experiment the trailing mask was triggered at the sentence level and not word-by-word as in the present research.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, individual differences in working memory and emotional intelligence can contribute to how nonliteral speech is interpreted. Superior working memory suppresses the literal meaning of ironic speech (Giora, 1999; Olkoniemi, Ranta, & Kaakinen, 2016; Olkoniemi, Johander, & Kaakinen, 2019), whereas the ability to recognize emotions aids irony comprehension (Nicholson, Whalen, & Pexman, 2013). There is also evidence that different communities of practice base their recognition of attitudes, intentions, and emotions in part on culturally defined factors such as overall communication style (directness vs. indirectness; Holtgraves, 1997; Rockwell & Theriot, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examined whether this slowdown is an implication of a reader resolving the sarcastic meaning (e.g., Olkoniemi et al, 2016), or whether it merely reflects a coherence break caused by the sarcastic statement, which contradicts the context in which it is presented. Finally, recent eye-tracking studies have shown that there are individual differences in how readers process sarcastic statements, and that these differences are related to the time-course of resolving the sarcastic meaning (Kaakinen et al, 2014; Olkoniemi, Johander, & Kaakinen, 2018; Olkoniemi et al, 2016). In the present study, we examined how the ability to recognise emotions and working memory capacity (WMC) are related to the processing of written sarcasm.…”
Section: Introductionmentioning
confidence: 99%